HUBUNGAN KAUSALITAS ANTARA PENERIMAAN PAJAK DAN PENGELUARAN NEGARA DI INDONESIA PERIODE 2000-2015 - Ridha Elvianti (Perpustakaan Universitas Surabaya, 2018)
This research intended to analyze the causal relationship between tax revenue and government expenditure in Indonesia. The data used in this research is secondary data form of time series. This research using the approach of quantitative with Unit Root Test and Granger Causality. The observation samples in this research is annual data in the period 2000-2015 and this study examines tax revenue causes government expenditures or vice versa. Augmented-Dickey Fuller (ADF) method indicates that the two variables have not stationary unit root on data level, but the two variables have a stationary unit root on first difference. Based on the result of granger causality test with a probability value of 0.7 which is below the critical value of 10% show that there is unidirectional causality from tax revenue to government expenditure.